Multivariate Analysis of Water Quality and Benthic Macrophyte Communities in Florida Bay, USA Reveals Hurricane Effects and Susceptibility to Seagrass Die-Off - Cole, Amanda M.; Durako, Michael J.; Hall, Margaret O. (Frontiers in Plant Science, 2018)
Seagrass communities, dominated by Thalassia testudinum, form the principal benthic ecosystem within Florida Bay, Florida USA. The bay has had several large-scale seagrass die-offs in recent decades associated with drought and hypersaline conditions. In addition, three category-5 hurricanes passed in close proximity to the bay during the fall of 2005. This study investigated temporal and spatial trends in macrophyte abundance and water quality from 2006 to 2013 at 15 permanent transect sites, which were co-located with long-term water quality stations. Relationships, by year and by transect location (basin), between antecedent water quality (mean, minimum and maximum for a 6-month period) and benthic macrophyte communities were examined using multivariate analyses. Total phosphorus, salinity, pH, turbidity, dissolved inorganic nitrogen (DIN), DIN to phosphate ratio (DIN:PO4-3), chlorophyll a, and dissolved oxygen correlated with temporal and spatial variations in the macrophyte communities. Temporal analysis (MDS and LINKTREE) indicated that the fall 2005 hurricanes affected both water quality and macrophyte communities for approximately a 2-year period. Spatial analysis revealed that five basins, which subsequently exhibited a major seagrass die-off during summer 2015, significantly differed from the other ten basins in macrophyte community structure and water quality more than 2 years before this die-off event. High total phosphorus, high pH, low DIN, and low DIN:PO4-3, in combination with deep sediments and high seagrass cover were characteristic of sites that subsequently exhibited severe die-off. Our results indicate basins with more mixed seagrass communities and higher macroalgae abundance are less susceptible to die-off, which is consistent with the management goals of promoting more heterogeneous benthic macrophyte communities.